D. Bahaliy in the Contemporary Ukrainian Historiography - Богдашина, Олена (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
In the article analyzed the works of Ukrainian authors devoted to the life and work of an outstanding historian and public figure. The facts prove a noticeable intensification of the study of the biography of a prominent Ukrainian during the last quarter century.The peculiarity of the modern period of the development of Bagalyі’s studies is its archeographic component, namely the publication of the correspondence D. Bagalyi, his manuscripts and the reprint of the most famous monographis of the historian.